Calculation of Cross-sectional Shape and Polar Moment of Inertia of a Thread Screw - Wang Baomin; Guo Hongfeng; Chai Xiaoyu (Jixie chuandong)
According to the characteristic of the trapezoidal thread screw,at first,the equation of the cross- section shape intersecting line is deduced,and according to the concept of polar moment of inertia in material mechanics and superposition principle,the accurate calculation formula of threaded screw polar moment of inertia is got. In the formula,when the thread tooth angle take different values,the tooth shape is the different thread.